Tender coconuts for nutritional security - Niral, V; Jerad, B Augustine; Jayasekhar, S; Chowdappa, P (Indian Horticulture, 2019)
In India, enterprising farmers in Tamil Nadu, especially in Pollachi and Coimbatore districts, have planted a sizeable coconut plantations with tender nut varieties for meeting the domestic demand are also for exploring avenues for tapping the export market. The trend is picking up in Kerala, Karnataka, Andhra Pradesh, Maharashtra and West Bengal. To enhance the profitability of growers and to avoid market fluctuations, growing tender nut varieties are strongly advocated.